Motivasi dan Pelimpahan Wewenang sebagai Variabel Moderating dalam Hubungan antara Partisipasi Penyusunan Anggaran dan Kinerja Manajerial - Slamet Riyadi (The Indonesian Journal of Accounting Research, 2013)
The relationship between budget participation and managerial performance has been attracting researchers’ attention. However, the result of previous studies on the relationship between budget participation and managerial performance has been inconclusive and often contradictory. One way to reconcile these conflicting results is to investigate the hypothesized relationship utilizing a contingency approach (Govindarajan, 1986a).This study empirically examined the effect of budget participation on managerial performance using a contingency approach. Two contingent variables were investigated, namely managerial motivation and delegation of authority. Mailed questionnaires were distributed to 340 managers from East Java manufacturing companies. The responses from 48 managers (14%) were analyzed by using regression analysis.The result indicated that the interaction between managerial motivation and budget participation did not direct affect managerial performance. But delegation of authority was found to have a significant effect on the relationship between budget participation and managerial performance will be high at higher levels of decentralization. In contrast, at low levels of decentralization (more centralization), the effect of budget participation on managerial performance will be low.